2020
DOI: 10.1093/ijnp/pyaa014
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of TRPC6 Mediated by PAX6 Hypomethylation Is Involved in the Mechanical Allodynia Induced by Chemotherapeutics in Dorsal Root Ganglion

Abstract: Background Although the action mechanism of antineoplastic agents is different, oxaliplatin, paclitaxel, or bortezomib as first-line antineoplastic drugs can induce painful neuropathy. In rodents, mechanical allodynia is a common phenotype of painful neuropathy for 3 chemotherapeutics. However, whether there is a common molecular involved in the different chemotherapeutics-induced painful peripheral neuropathy remains unclear. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…9a, b and 10b, f), suggesting that TRPC6 plays an important role in the faciliation of neuropathic pain and microgliosis. These results are in concert with the recent studies demonstrating the role of TRPC6 in varied chronic pain, such as neuropathic pain, cancer pain and morphine induced pain [12,50,53]. Thus, TRPC6 may be an important and promising molecular target for the management of chronic pain.…”
Section: The Non-effects Of La On Astrocytessupporting
confidence: 82%
“…9a, b and 10b, f), suggesting that TRPC6 plays an important role in the faciliation of neuropathic pain and microgliosis. These results are in concert with the recent studies demonstrating the role of TRPC6 in varied chronic pain, such as neuropathic pain, cancer pain and morphine induced pain [12,50,53]. Thus, TRPC6 may be an important and promising molecular target for the management of chronic pain.…”
Section: The Non-effects Of La On Astrocytessupporting
confidence: 82%
“…Mechanical and heat hypersensitivity TRPA1 [65,69,70] Increased functional activity in terms of hypersensitivity to stimuli [65,69,70] Mechanical and cold hypersensitivity TRPC6 [71] Increased expression in DRG (through DNMT3b-mediated PAX6 gene hypomethylation) [71] Mechanical hypersensitivity TRPM8 [70] Increased functional activity in terms of hypersensitivity to stimuli [70] Mechanical and cold hypersensitivity Table 2. Increased expression of voltage-gated channels following paclitaxel treatment.…”
Section: Name Channel Direction Of Regulationmentioning
confidence: 99%
“…This analysis showed that DNA motifs targeted by several TFs, including mainly EBF, PAX, DLX, LHX, and HNF family members, as well as En1, Nkx6.1, PRDM1, and Nanog transcription factors, were statistically significantly enriched in the regions harboring BTZ-induced methylation changes ( q -value ≤ 0.05) ( Supplementary Table S5 ). All of these TFs have previously been linked to neurogenesis or neuronal differentiation [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]; most interestingly, the top two identified TFs, PAX6 and EBF2, have been shown to be associated with peripheral neuropathy [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The transcription factor binding sites that were enriched for the BTZ-induced methylation changes were EBF, PAX, DLX, LHX, and HNF family members, but also several other TFs, such as En1, Nkx6.1, PRDM1 and Nanog, all of which have previously been linked to neurogenesis or neuronal differentiation [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The top hit in this analysis was for PAX6, which has been shown to contribute to the painful sensation, referred to as mechanical allodynia, following applications of different chemotherapeutics treatments, including BTZ [ 37 ]. The second top transcription factor, EBF2, was shown in in vivo studies to play a key role in neuronal migration and nerve development [ 38 ].…”
Section: Discussionmentioning
confidence: 99%